Textual Function In A Little Golden Book: My Name Is Elmo Series - masriani silalahi; Rani Rakasiwi; Nurmaliana Sari (Jurnal Scientia, 2022)
This study deals with Theme and Rheme in A Little Golden Book. The objectives of the research were to find out the most dominant type of theme used in A Little Golden Book especially in My Name is Elmo Series.The sentences in A Little Golden Book: My Name is Elmo Series is 41 sentences used as the source of data in this research. This research was performed by using the descriptive qualitative method. The technique for analyzing data were typing all the sentences in Ms. Word to be printed out, separating each sentences to be analyzed based on the story of pages, analyzing every sentences in the column of the sentence based on the types of theme, classifying the theme based on the type of Simple Theme, calculating the percentage of each theme, finding out the dominant type of theme in A Little Golden Book: My Name is Elmo Series.The findings indicated that Simple Theme there were 87.80% of Theme (Unmarked) and 12.20% of Theme (Marked). It means that the dominant type of Simple Theme in Oprah Winfrey was Theme (Unmarked) that was 87.80%.